Doctor's Legal Protection in Health Services for Covid-19 Patients - Helena Primadianti Sulistyaningrum; Dian Afrilia; Theta Murty (Research Collaboration Community (RCC), 2022)
Doctors as medical workers are at the forefront of health services for Covid-19 patients. During the pandemic, doctor is the profession that has the highest risk in handling Covid-19 patients. In this case, it is appropriate if doctors get legal protection in carrying out their profession. So, what is the actual form of legal protection that doctors have received so far in handling Covid-19 patients? Have the existing regulations accommodated this protection?. The method of research which used in this research was normatif by examining the law which is conceptualized as a norm or rule that applied in society, and becomes a reference for everyone's behavior. The results of the study indicated that there were preventive and repressive measures which were as means of legal protection for doctors during Pandemic. Preventive efforts can be interpreted as steps or ways that can be taken to prevent an event that has legal consequences in the form of fulfilling obligations as a doctor, namely by carrying out the profession in accordance with professional standard, professional service standard, and standard operating procedures, completing administration in medical practice such as informed consent. and medical records, getting vaccines, providing incentives. While repressive efforts are defined as steps or method which taken if an event that results in law has occurred in the form of providing compensation to doctors who died, giving awards for services, bearing medical expenses for exposed doctors, and prosecution for criminal acts towards people who do not orderly implement health protocols. The legal protection of medical workers in handling Covid-19 is evident in the fact that these medical workers have received legal protection in the form of supervision and guidance carried out by the Central Government, Regional Government or their Work Agencies. It shows that existing regulations have accommodated legal protection for doctors during the Covid-19 pandemic.